Factors influencing work-life balance among married women employees in Putra Specialist Hospital Melaka / Nurul Nabila Azman - Azman, Nurul Nabila (Faculty of Business and Management, 2018)
In today’s world, the concept “work-life balance” is considered to be one of the major issues that play an important role in organizational success. However, work-life balance is seen differently in different society. This paper aims to find out the reasons, which create work-life imbalance. Nowadays, a female employee faces more difficulties to balance between work and life than a male employee. This study focuses on married women employees in non-clinical departments. This study has been conducted based on primary research where a sample of 44 married women employees from different organizations is selected. Moreover, as for the sampling method in this study the researcher has use a non-probability sampling which is a convenience sampling as a sampling technique. Questionnaire was taken to reveal the factors that lead to the reason on an imbalance work-life. The study shows that the factors for which female employees are facing trouble to maintain a work-life balance are mostly because of family, work overload, working hours and work environment. The finding of the study focuses on formulating a structured guideline for the company so that the above mentioned factors can be omitted and female employees can balance their professional and personal life to get a better life in the future.